TETRACYCLINE ANTIBIOTIC REMOVAL FROM AQUEOUS SOLUTION USING CLADOPHORA AND SPIRULINA ALGAE BIOMASS - Abd, I. N.; Mohammed-Ridha, M. J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Cladophora and Spirulina algae biomass have been used for the removal of Tetracycline (TC) antibiotic from aqueous solution. Different operation conditions were varied in batch process, such as initial antibiotic concentration, different biomass dosage and type, contact time, agitation speed, and initial pH. The result showed that the maximum removal efficiencies by using 1.25 g/100 ml Cladophora and 0.5 g/100 ml Spirulina algae biomass were 95% and 94% respectively. At the optimum experimental condition of temperature 25°C, initial TC concentration 50 mg/l, contact time 2.5hr, agitation speed 200 rpm and pH 6.5. The characterization of Cladophora and Spirulina biomass by Fourier transform infrared (FTIR) indicates that the presence of functional groups of different components such as the Hydroxyl group (-OH), amides(N-H stretch) were responsible of surface adsorption processes. The isothermal study has been applied using Freundlich, Temkin, and Langmuir models. The data best fitted with the Langmuir model. Finally, The pseudo-second-order kinetic model was best fitted the kinetic data with a high coefficient of determination (R2< 0.97 and 0.99) when used Cladophora and Spirulina algae biomass, respectively. The study showed that both Cladophora and Spirulina algae were promising and economical biomass that could be used for a large scale bioreactor.